2017
DOI: 10.1108/rpj-04-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of selective laser melting parameters for the Ni-based superalloy IN-738 LC using Doehlert’s design

Abstract: Purpose The Ni-based superalloy IN-738 LC is known to be susceptible to porosity and different types of cracking during the build-up process and, thus, challenging to manufacture using selective laser melting (SLM). Determining a feasible set of operating parameters for SLM of nickel-based superalloys involves new approach to experimental design based on the Doehlert method that assists in determining an optimal (feasible) set of operating parameters for SLM of IN-738 LC powder alloy. Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…When hatching distance is low, the high relative density parts are easily to obtain. This can also be found in other studies [9,19,20,22]. The SLMed AlSi10Mg alloy samples with the combination of higher laser power, higher scan speed, and lower hatching distance also have higher ultimate tensile strength (UTS) and yield strength [18].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…When hatching distance is low, the high relative density parts are easily to obtain. This can also be found in other studies [9,19,20,22]. The SLMed AlSi10Mg alloy samples with the combination of higher laser power, higher scan speed, and lower hatching distance also have higher ultimate tensile strength (UTS) and yield strength [18].…”
Section: Discussionsupporting
confidence: 72%
“…The two combinations of parameters are both near to the energy density, which corresponds to the highest relative density in Figure 2. In Figure 3, the micro-pores can be observed in the samples built with large hatching distance and high scan speed-this phenomenon was also observed in other alloys [10,22].…”
Section: Optimization Of the Slm Processing Parameterssupporting
confidence: 63%
See 2 more Smart Citations
“…In the case of laser metal deposition (by powder feeding), which uses a high-power laser beam to directly spray and deposit metal powder, it has the advantage of greater manufacturing speed, capability of producing relatively larger parts and application to 3D-shaped base metals compared to powder bed deposition, and these advantages were utilized in attempts to manufacture bulk and coating layers with Nibased super alloys. 1116) Previous studies have reported microstructural interpretation according to variables concerning the manufacturing process, 11,15) defect formation such as pores and cracks. 11,13) Most studies present the basic mechanical properties of Ni-based materials manufactured with additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%